Phytochemical properties of essential oil from Artemisia sieberi Besser (Iranian accession) and its antioxidant and antifungal activities. Issue 21 (2nd November 2021) - Ghasemi, Ghader; Alirezalu, Abolfazl; Ishkeh, Shirin Rahmanzadeh; Ghosta, Youbert
Abstract: In this study, the phytochemical profile, the essential oil composition of an Iranian accession of Artemisia sieberi and their antioxidant and antifungal properties were investigated. The amount of essential oil yield was 1.5% (w/v) and twenty two components were identified by GC-MS analysis being camphor (33.64%), 1, 8-cineole (25.66%) and chrysanthenone (7.86%) the major compounds. The amount of total polyphenols and flavonoids, total ascorbic acid and carotenoid content of A. sieberi extract were determined, and resulted in 666.26 mg GAE/100g DW, 54.77 mg QUE/100g DW, 153.585 mg/100g DW, and 907.18 mg/100g FW, respectively. Highest antioxidant activity based on DPPH bioassay was recorded in essential oil (84.04%) and extract (89.33%). Furthermore, the essential oil of A. sieberi tested for its antifungal activity, demonstrated to reduce significantly the mycelium growth rate of Botrytis cinerea, that is, no mycelial growth was observed at concentrations 1000 and 1500 μll −1 . Graphical Abstract: